2018
DOI: 10.18520/cs/v114/i12/2543-2548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Potassium Solubilizing Bacteria from Crop Rhizosphere of the North Eastern Region of India

Abstract: In this study, isolation and characterization of potassium solubilizing bacteria (KSB) have been carried out which could solubilize a substantial amount of potassium (K) following incubation with mica. Five KSB, isolated from banana and chilli rhizosphere were identified by 16S rDNA sequence analysis. The identified bacteria were Klebsiella sp. and Bacillus cereus. The isolates had K solubilization potential within the range of 76.3-78.42% compared to control along with significant drop in pH (4.62-4.86). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The soil pH was significantly reduced to 7.7 as a result of KSB inoculation, especially in the treatments that contained potassium sulfate alone or mixed with K-feldspar. Several previous researchers have confirmed the ability of B. cereus to produce organic acids and reduce the soil pH [16,[42][43][44]. According to the results of our study, the soil pH in the treatments inoculated with the bio-fertilizer was lower than that of the non-inoculated ones.…”
Section: Soil Qualitysupporting
confidence: 81%
See 3 more Smart Citations
“…The soil pH was significantly reduced to 7.7 as a result of KSB inoculation, especially in the treatments that contained potassium sulfate alone or mixed with K-feldspar. Several previous researchers have confirmed the ability of B. cereus to produce organic acids and reduce the soil pH [16,[42][43][44]. According to the results of our study, the soil pH in the treatments inoculated with the bio-fertilizer was lower than that of the non-inoculated ones.…”
Section: Soil Qualitysupporting
confidence: 81%
“…Chen et al [43] studied the activity of potassium solubilizing bacteria (B. aryabhattai SK1-7) in fermentation and pot experiments, and they found that the pH of the growth media declined from 7.2 to 4.3 within the first day, while the soil pH in the pot experiments was decreased by 0.28 units after 100 days of inoculation. The decreases in the soil pH as a result of inoculation with KSB was also reported by Buragohain et al [44]. The indirect effect of the biofertilizer was through increasing the plant growth as a result of stimulating hormones produced from the inoculated biofertilizer [45,46].…”
Section: Soil Qualitysupporting
confidence: 72%
See 2 more Smart Citations
“…Also fluctuation in soil pH is critical to soil potassium kinetics and release from their respective sources by microbes including bacteria (Ahmad et al, 2016;Shrivastava et al, 2016;Estesami 2017;Masood and Bano, 2017;Sattar et al, 2019;Kour et al, 2020). According to Chen et al (2020), pH decline to 3.3 resulted in approximately 32.6% increase in the concentration of soil potassium and this is affirmed by the study of Buragohain et al (2018).…”
Section: Factors That Affect the Solubilization Of Potassium By Potas...mentioning
confidence: 97%